Highly Robust Non‐Noble Alkaline Hydrogen‐Evolving Electrocatalyst from Se‐Doped Molybdenum Disulfide Particles on Interwoven CoSe2 Nanowire Arrays. Issue 13 (4th March 2020) - Liao, Liling; Sun, Jingying; Li, Dongyang; Yu, Fang; Zhu, Yijun; Yang, Yi; Wang, Jinjian; Zhou, Weichang; Tang, Dongsheng; Chen, Shuo; Zhou, Haiqing
Abstract: Developing efficient non‐noble and earth‐abundant hydrogen‐evolving electrocatalysts is highly desirable for improving the energy efficiency of water splitting in base. Molybdenum disulfide (MoS2 ) is a promising candidate, but its catalytic activity is kinetically retarded in alkaline media due to the unfavorable water adsorption and dissociation feature. A heterogeneous electrocatalyst is reported that is constructed by selenium‐doped MoS2 (Se‐MoS2 ) particles on 3D interwoven cobalt diselenide (CoSe2 ) nanowire arrays that drives the hydrogen evolution reaction (HER) with fast reaction kinetics in base. The resultant Se‐MoS2 /CoSe2 hybrid exhibits an outstanding catalytic HER performance with extremely low overpotentials of 30 and 93 mV at 10 and 100 mA cm –2 in base, respectively, which outperforms most of the inexpensive alkaline HER catalysts, and is among the best alkaline catalytic activity reported so far. Moreover, this hybrid catalyst shows exceptional catalytic performance with very low overpotentials of 84 and 95 mV at 10 mA cm –2 in acidic and neutral electrolytes, respectively, implying robust pH universality of this hybrid catalyst. This work may provide new inspirations for the development of high‐performance MoS2 ‐based HER electrocatalysts in unfavorable basic media for promising catalytic applications. Abstract : A heterogeneous catalyst constructed by selenium‐doped molybdenum disulfide particles supporting on interwoven cobalt diselenide nanowire arrays is developed to exhibit promising pH‐universal hydrogen evolution with extremely low overpotentials of 30 and 93 mV at 10 and 100 mA cm –2 in base solution, and also very low overpotentials of 84 and 95 mV at 10 mA cm –2 in acidic and neutral electrolytes, respectively.